Comparison of the Full Outline of Unresponsiveness Score with the Glasgow Coma Scale as a Coma Assessment Scale in Pediatric Intensive Care - Misirlioglu, Merve; Yildizdas, Dincer; Ekinci, Faruk; Ozgur Horoz, Ozden; Mert, Gulen Gul (Journal of Pediatric Neurology, 2021)
Rapid assessment of cerebral dysfunction is crucial for the management of patients in intensive care units. The Glasgow Coma Scale (GCS) evaluates eye, verbal, and motor responses, but is insufficient to effectively evaluate patients on mechanical ventilation, or who are unable to speak. The Full Outline of Unresponsiveness (FOUR) score includes additional information such as brainstem reflexes and respiratory status to provide a more complete clinical assessment. In this study, we aimed to compare the FOUR score with GCS in the assessment of patients with coma. This prospective study included patients between 1 month and under 18 years of age, who were hospitalized in the pediatric intensive care unit due to risk of coma or ongoing impairment of consciousness between May 2018 and June 2019. Information regarding FOUR scores, GCS values, patient demographics, duration of hospitalization, requirement for mechanical ventilation, and patient comorbidities were recorded and analyzed. Among the 80 patients included in the study, a statistically significant correlation was found between (low) GCS and FOUR scores during admission, and mortality and requirement for mechanical ventilation. Monitoring the level of consciousness is important in pediatric intensive care units and may be predictive of the course and disease outcome. Similar to the GCS, the FOUR score is a good indicator for predicting mortality and requirement for mechanical ventilation.
Keywords: impairment of consciousness; glasgow coma scale; full outline of unresponsiveness score; pediatric intensive care